Dining with John : communal meals and identity formation in the Fourth Gospel and its historical and cultural context - Kobel, Esther, 1977- (Biblical Interpretation Series, 2011)
This book explores the accounts of communal meals and the metaphorical use of food and drink language in the narrative world of the Gospel of John. It argues that the Johannine community regularly gathered for communal meals in which the food and drink on the menu would have taken on a spiritual significance far exceeding the physical sustenance. The study employs a socio-rhetorical methodology and consequently moves from text to context. It tentatively describes the texts' influence on the formation of early Christian identity and suggests that the Johannine meal accounts provide a way to imagine the demographic composition of the community and its historical context.